2015
DOI: 10.1212/nxi.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Fcγ receptor expression in patients with CIDP

Abstract: Objective:To evaluate the expression of activating and inhibitory Fc-gamma receptors (FcγRs) before and during clinically effective therapy with IV immunoglobulin (IVIg) in patients with chronic inflammatory demyelinating polyneuropathy (CIDP).Methods:Peripheral blood leukocyte subsets, including classical CD14highCD16− and nonclassical inflammatory CD14lowCD16+ monocytes as well as naive CD19+CD27− and memory CD19+CD27+ B cells, were obtained at baseline and monitored at 2 and 4–8 weeks after initiation of IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In exploring the underlying disease-mediated mechanism that caused FcγRIIB dysregulation, the authors examined single nucleotide polymorphisms on the FcγRIIB promotor and found that 43% of their CIDP samples were heterozygous for a 386C/120A variant on the promotor whereas <5% of healthy controls possessed this polymorphism. In a similar study by Quast and colleagues, CIDP patients were found to possess decreased mean fluorescence intensity of FcγRIIB on both naïve and memory B cells and CD14 high CD16 - monocytes compared to controls [ 51 ]. The CIDP patients also had increased mean fluorescence intensity of FcγRI on both CD14 high CD16 - and CD14 low CD16 + monocytes and increased FcγRIIA on CD14 low CD16 + monocytes compared to controls.…”
Section: Typical Cidpmentioning
confidence: 99%
“…In exploring the underlying disease-mediated mechanism that caused FcγRIIB dysregulation, the authors examined single nucleotide polymorphisms on the FcγRIIB promotor and found that 43% of their CIDP samples were heterozygous for a 386C/120A variant on the promotor whereas <5% of healthy controls possessed this polymorphism. In a similar study by Quast and colleagues, CIDP patients were found to possess decreased mean fluorescence intensity of FcγRIIB on both naïve and memory B cells and CD14 high CD16 - monocytes compared to controls [ 51 ]. The CIDP patients also had increased mean fluorescence intensity of FcγRI on both CD14 high CD16 - and CD14 low CD16 + monocytes and increased FcγRIIA on CD14 low CD16 + monocytes compared to controls.…”
Section: Typical Cidpmentioning
confidence: 99%
“…Other putative mechanisms of IVIg efficacy include the neutralization of autoantibodies, inhibition, and abrogation of the activated complement, and alteration of Fc‐receptor expression 38 . Increased expression of the activating Fc gamma I receptors on monocytes and a reduced expression of the inhibitory Fc gamma IIb receptors on naïve and memory B cells, as well as on monocytes, has been found in the blood from CIDP patients before IVIg treatment, whereas they were partly restored after IVIg 44 . These findings indicate the complexity of the influence of IVIg on macrophage‐induced demyelination.…”
Section: Therapeutic Insightsmentioning
confidence: 99%
“…On the other hand, thyrocytes are known to produce granulocyte/macrophage colony-stimulation factor (GM-CSF), which was found to antagonize the TGF-β induced expression of FcyRIII on human monocytes [ 38 , 39 ]. Deregulation of Fcγ receptors expression was found in the course of few human diseases, however, any functional relevance remains to be determined [ 40 , 41 ]. Increased expression of the CD16 molecule on the surface of leukocytes was reported in several inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%